البنائية لتعلم اللغة العربية التوصلي على أساس علم اللغة العربية الإجتماعي - Nadia Imelda; Nurelisa Putri Ayu; Marhamah Ulfa; Abdul Moneim Abdullah Khalaf (Arabiyyatī: Journal of Arabic Language Education, 2024)
This research investigates the application of a constructivist approach in the context of Arabic language learning, focusing on the communicative aspects, with a theoretical foundation based on sociolinguistics. The main objective of this study is to explore how the constructivist approach can be optimized in the context of sociolinguistics-based Arabic language learning to enhance students' communication skills. A qualitative research method is used to gain an in-depth understanding of the learning process and students' experiences in developing their Arabic language proficiency. Data collection techniques involve classroom observations, interviews with teachers, and document analysis. The results of the study indicate that the constructivist approach applied in Arabic language learning can motivate students, enable student-centered learning, and integrate social and cultural aspects into the learning process. The implications of this research highlight the importance of adopting a contextual and student-oriented approach in Arabic language teaching, taking into account social, cultural, and communicative aspects of language learning. These findings provide significant contributions to practical and theoretical understanding in the development of effective and contextual Arabic language learning methods. Keywords: Constructivism, Arabic Language Learning, Communicative, Sociolinguistics